Analysis of inflammatory cells and mediators in skin wound biopsies to determine wound age in living subjects in forensic medicine. (February 2015) - Fronczek, Judith; Lulf, Ronald; Korkmaz, H. Ibrahim; Witte, Birgit I.; van de Goot, Franklin R.W.; Begieneman, Mark P.V.; Schalkwijk, C.G.; Krijnen, Paul A.J.; Rozendaal, Lawrence; Niessen, Hans W.M.; Reijnders, Udo J.L.
Highlights: A new method to determine wound age in living subjects. Inflammatory cells and mediators in wound age determination in living subjects. The introduction of a probability scoring system for wound age estimation in living subjects. Abstract: Objective: In forensic medicine it is important to determine the age of skin wounds in living subjects. The aim of this study was to assess whether analysis of inflammatory cells and inflammatory mediators in skin biopsies of wounds from living subjects could improve wound age determination. Methods: Biopsies ( n = 101), representing the superficial border area of a skin wound, were taken from skin injuries of known wound age (range: 4.5 hours to 25 days) of living subjects. All biopsies were analyzed for 3 inflammatory cell markers (MPO, CD45 and CD68) and 4 inflammatory mediators (MIP-1, IL-8, CML and vitronectin). For quantification, biopsies were subdivided in 4 different timeframes: 0.2–2 days, 2–4 days, 4–10 days and 10–25 days old wounds. Subsequently, a probability scoring system was developed. Results: MPO, CD45, MIP-1, IL-8 (inflammatory cell markers) and N(epsilon)-(carboxymethyl)lysine (CML) positivity were maximal in wounds of 0.2–2 days old and then decreased in time. Remarkably, CD45, CD68 and CML showed a minor but non-significant increase again in 10–25 days old wounds. MPO and CD68 positivity was significantly lower in 4–25 days old wounds compared to 0.2–4 days old wounds. MPO positivity was also significantly lower in 10–25 days old wounds compared to 0.2–10 days old wounds. For CD45, MIP-1, IL-8 and CML no significant differences between the age groups were found. In case of vitronectin positivity in the extravasate or when the number of MIP-1 or IL-8-positive cells was more than 10 cells/mm 2 the probability that a wound was more than 10 days old was 0%. A probability scoring system of all analyzed markers can be used to calculate individual wound age probabilities in biopsies of skin wounds of living subjects. Conclusions: We have developed a probability scoring system of inflammatory cells and mediators that can be used to determine wound age in skin biopsies of living subjects.